Exploring the Clinical and Investigational Profile of Females With Hirsutism at a Tertiary Care Center - Shah, Pooja; Chaudhary, Raju; Agarwal, Pooja; Baxi, Kalgi (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Introduction: Hirsutism is a common clinical condition with multifactorial etiology, ranging from endocrinological abnormalities to benign idiopathic causes to, rarely, severe malignant disorders. It negatively impacts the quality of life and self-esteem of affected women, necessitating proper etiological diagnosis and management. Aims and objectives: To evaluate etiology of hirsutism and study clinical manifestations and biochemical characteristics associated with it. Materials and Methods: After obtaining approval from Institutional Ethics Committee, a cross-sectional observational study was conducted at the tertiary care hospital for 2 years. Detailed history, clinical examination, assessment of hirsutism as per modified Ferriman Gallwey score, investigations including hormonal assays and radiological examination were done for all patients. Data were analyzed using appropriate statistical tests. Results: Among 43 women, 65.11% had mild hirsutism, 25.58% had moderate, and 9.30 % had severe hirsutism. Menstrual irregularities were noted in 58.14%, and 13.95% had a family history of hirsutism. Acne (65.11%) and seborrhea (51.16%) were the most common cutaneous findings. 16.28 % and 27.91% women were overweight and obese, respectively. Insulin resistance (Homeostasis Model Assessment of Insulin Resistance i.e., HOMA IR index >2) was present in 46.51% patients, with PCOS (Polycystic Ovary Syndrome) being the leading cause, and showed significant correlation with BMI (p = 0.001). LH/FSH ratio >2 (i.e., ratio of Luteinizing Hormone to Follicle-Stimulating Hormone) was present in 39.53% and 46.5 % recorded positive findings of polycystic ovarian morphology by radiological examination. Conclusion: The most common cause of hirsutism in our study was found to be PCOS, followed by idiopathic hirsutism. Diligent assessment of hirsute women with particular attention to metabolic components such as insulin resistance, as indicated by the HOMA-IR index, must be undertaken to identify the root cause and tailor appropriate interventions.